Pengaruh Biochar Terhadap Mobilitas Merkuri (Hg) Pada Percobaan Pencucian (Leaching) Tertutup: Effect of Biochar on Mercury (Hg) Mobility in a Closed Leaching Experiment - Baiq Eliza Prizma Mahardhika; Sukartono Sukartono; I Gusti Made Kusnarta; Suwardji Suwardji; Fahrudin Fahrudin (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
This study aims to determine the effect of biochar application on Hg mobility in a closed leaching experiment using gold processing tailings contaminated soil. The factorial experiment was set up using a Completely Randomized Design (RBD) which tested three types of biochar (rice husk biochar, coconut shell, and corncob biochar) and three doses of biochar (0.10 tons ha-1 and 15 tons ha-1). The PVC column containing a mixture of polluted soil and dibiochar was washed four times with deionized water for a total of 1090 ml of watering. The results showed that the application of biochar can reduce the mobility of mercury (Hg) in small scale gold processing tailings polluted soils. The dissolved Hg concentration in the leachate decreased with increasing dose of biochar application. Leachate from corn cob biochar (15 tons ha-1) treatment showed the lowest Hg concentration of 0.0012 ppm but was not significantly different from leachate from the soil column that was applied coconut shell and rice husk biochar. The concentration of Hg in the leachate for all biochar treatments ranged from 0.0012 - 0.0062 ppm, significantly different from the leachate concentration of the soil column without biochar, which was 1.62 ppm. This provides an indication that biochar can reduce the leaching rate, so that the concentration of Hg is not much leached into the soil. Therefore, biochar can be used as a soil enhancer in remediation of mercury (Hg) polluted soil so that it can slow down the mobility of mercury (Hg) so that it has a small impact on the environment.